2011
DOI: 10.1177/1548051811405208
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing: The Influences of Learning Organization Culture, Organizational Commitment, and Organizational Citizenship Behaviors

Abstract: This study investigated cultural (learning organization culture), psychological (organizational commitment), and behavioral (organizational citizenship behavior) antecedents of knowledge-sharing intention of employees. The authors' structural equation model using data collected from 452 Korean workers showed that learning organization culture was significantly associated with organizational commitment, organizational citizenship behavior, and knowledge-sharing intention. Organizational citizenship behavior tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 59 publications
4
53
0
Order By: Relevance
“…The second, the willingness of employees toward collecting and sharing knowledge is suggested having positive effect on many key outcomes of an organization such as organizational performance (Garcıa-Morales et al, 2008;Wang et al, 2016); employees' affective commitment (Li et al 2015); organizational citizenship behaviors (Jo et al, 2011) and so on. However, few researches test the influence of KS on competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…The second, the willingness of employees toward collecting and sharing knowledge is suggested having positive effect on many key outcomes of an organization such as organizational performance (Garcıa-Morales et al, 2008;Wang et al, 2016); employees' affective commitment (Li et al 2015); organizational citizenship behaviors (Jo et al, 2011) and so on. However, few researches test the influence of KS on competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al (2012); Sorakraikitikul and Siengthai (2014) identified that organizational learning culture as a factor influenced knowledge sharing behavior. Equally, Jo and Joo (2011); Islam et al (2012) agreed that organizational learning culture has a significant influence on OCB. OCB was also found to be a significant mediator variable on knowledge sharing behavior (Jo and Joo, 2011;Islam et al, 2012;Sadegh, 2015;Husain et.…”
Section: Introduce the Problemmentioning
confidence: 99%
“…Equally, Jo and Joo (2011); Islam et al (2012) agreed that organizational learning culture has a significant influence on OCB. OCB was also found to be a significant mediator variable on knowledge sharing behavior (Jo and Joo, 2011;Islam et al, 2012;Sadegh, 2015;Husain et. al., 2017).…”
Section: Introduce the Problemmentioning
confidence: 99%
“…Yet again, a number of studies have attempted to discover significant factors that facilitate or impede knowledge sharing. However, knowledge sharing is too complex of a process to be explained by one single factor or a few factors (Jo and Joo, 2011). Furthermore, prior studies have been trying to recommend a one size fits all kind of solutions to reward and knowledge sharing system.…”
Section: Introductionmentioning
confidence: 99%